Prognostic and clinical correlates of angiographically diffuse non-obstructive coronary lesions. Issue 9 (15th August 2003) - Bigi, R; Cortigiani, L; Colombo, P; Desideri, A; Bax, J J; Parodi, O
Abstract : Objective: To make a prospective assessment of the clinical and prognostic correlates of angiographically diffuse non-obstructive coronary lesions. Design: Angiographic vessel and extent scores were calculated in 228 clinically stable patients (mean (SD) age, 60 (11) years; 43 women, 185 men) undergoing prospective follow up for the composite end point of death and myocardial infarction. The effect on outcome of clinical variables (age, sex, previous myocardial infarction, diabetes mellitus, smoking habit, systemic hypertension, hypercholesterolaemia, ejection fraction) and angiographic variables (vessel and extent score) was evaluated by Cox's proportion hazard model. Results: The vessel score was 3 in 34 patients (15%), 2 in 78 (34%), 1 in 87 (38%), and 0 in 29 (13%). Median extent score was 60 (range 6–110; first quartile 40, third quartile 70). Forty one events (nine deaths and 32 myocardial infarcts) occurred over a median follow up period of 30 months. Age and extent score were the only multivariate predictors of outcome, but the latter provided 28% additional prognostic information after adjustment for the most predictive variables (gain in χ 2 = 7, p < 0.01). A vessel score of 3 was associated with worse survival, while no significant discrimination was possible among the other groups. However, assignment of patients to two groups according to an ROC curve derived cut off value for the extent score made it possible to obtain significant discrimination of survival even in cases with vessel scores of 0 to 2. Age and diabetes were clinical markers of a higher extent score. Conclusions: The angiographic extent score is a powerful marker of adverse outcome independent of severity and the number of flow limiting coronary lesions, and may reflect the link between clinical risk profile and diffusion of coronary atherosclerosis. Thus it should be of clinical value for targeting aggressive preventive measures.